Gender Violence as Global Phenomenon: Refugees, Genital Surgeries, and Neocolonial Projects of the United States. (August 2016) - McKinnon, Sara L.
This essay investigates the mounting U.S. vision of gender violence since the 1990s as a global phenomenon. Focusing on U.S. legal, political, and media discourse about female circumcision in particular, and gender violence more broadly, this essay examines what U.S. imaginaries about global gender violence enable as warrants for neocolonial consolidations of U.S. power in the 21st century through international projects and programs of defense, development, and diplomacy. The essay first addresses the way female circumcision becomes recognized in the United States imaginary as a gendered violence that is distant from the United States and essential to the African continent and African women's bodies. It then questions what the recognition of gender violence as a global phenomenon does for U.S. neocolonial projects of defense, development, and diplomacy. It is the flexibility of gender violence as a rhetoric—its ability to be both specific and general—that makes it most potent in the service of U.S. neocolonial practices and projects around the world.